Analysis of Factors Affecting the Integrity of Financial Statements: The Role of the Audit Committee, Company Size, and Leverage - Yonson Pane (Outline Publisher, 2026)
This research analyzed the factors influencing financial statement integrity among companies listed on the Indonesia Stock Exchange during the 2022 fiscal year. The study examined the roles of the audit committee, company size, and leverage as primary determinants of reporting honesty. It integrated the alignment between financial data and non-financial disclosures in sustainability reports to identify potential greenwashing practices that could mislead stakeholders. A quantitative approach was employed, utilizing multiple linear regression analysis to evaluate the relationships between the variables. The researcher selected the sample through purposive sampling, focusing on issuers that provided complete annual and sustainability reports. The results indicated that the audit committee and company size exerted a positive and significant influence on financial statement integrity. These findings suggested that independent oversight and reputational risks associated with large organizations effectively reduced information asymmetry. Conversely, leverage demonstrated a negative and significant impact, which implied that high debt burdens encouraged opportunistic managerial behavior through earnings management. This study offered practical contributions for regulators and investors in evaluating corporate information credibility during an era of increasing environmental, social, and governance transparency and digital reporting integration.